2010
DOI: 10.1177/1533317510382892
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes of the Human Purkinje Cells and Deposition of Neuritic Plaques and Neurofibrillary Tangles on the Cerebellar Cortex of Alzheimer’s Disease

Abstract: Alzheimer's disease is a neurodegenerative disorder, characterized by progressive decline in memory and in social performance. The morphological hallmarks of the disease are neuronal loss, loss of dendritic spines, neurofibrillary degeneration and neuritic plaques mainly in the hippocampus and the cortex of the cerebral hemispheres. This study is based on the morphological analysis of the cerebellar cortices of eight brains, 4 patients suffered from Alzheimer's disease and 4 normal controls, by Golgi method, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 20 publications
(26 reference statements)
2
52
0
3
Order By: Relevance
“…In previous studies of ours using the Golgi method and 3D neuronal reconstruction techniques, severe dendritic and spinal alterations were seen in Alzheimer's disease and normal aged brains [18][19][20].…”
Section: Communicating Authormentioning
confidence: 65%
See 2 more Smart Citations
“…In previous studies of ours using the Golgi method and 3D neuronal reconstruction techniques, severe dendritic and spinal alterations were seen in Alzheimer's disease and normal aged brains [18][19][20].…”
Section: Communicating Authormentioning
confidence: 65%
“…Histological criteria for the diagnosis of AD were those outlined by the National Institutes of Health/American Association of Retired Persons (NIH/AARP) Research Workshop on the Diagnosis of Alzheimer's Disease. All cases fulfilled the histological criteria for AD [18].…”
Section: Materials and Methods Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies based on Golgi staining and electron microscopy have revealed dendritic and spinal changes in the prefrontal cortex, cerebellum and visual and acoustic cortices [9,10], which consisted mostly of a tremendous decrease of spine density, spinal poverty and loss of the distal dendritic spines. In addition, the morphometric estimation of the dendritic branches and spines of early cases of Alzheimer's disease revealed a 45% reduction of branches of the apical and the basal dendrites and a 52% reduction of dendritic spines in the acoustic and visual cortices [11].…”
Section: Editorialmentioning
confidence: 99%
“…Electron microscopy revealed substantial synaptic alterations between mossy fibers and granule cell dendrites, characterized by polymorphisms, paucity of synaptic vesicles and marked mitochondrial alterations [12]. In the cerebellar cortex, morphometric estimation revealed a 43% reduction of Purkinje cell dendritic spines and a 16% increase in the length of the spines, associated with marked abridgment of dendritic arborization, which covered only 61% of the depth of the molecular layer [11].…”
Section: Editorialmentioning
confidence: 99%